2017
DOI: 10.3390/en10091253
|View full text |Cite
|
Sign up to set email alerts
|

Status Quo of the Air-Conditioning Market in Europe: Assessment of the Building Stock

Abstract: This study fills in knowledge gaps for the European air-conditioning (AC) market, which is fundamentally important to raising awareness about primary energy utilization. In contrast to space heating (SH) and domestic hot water (DHW) preparation, the European Union (EU) AC market is barely explored in scientific literature. While the focus of previous research has been on the residential sector, a shortfall of data for the services (wholesale and retail, offices, education, health, hotels and bars) exists. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…Based on the methodology proposed by Pezzutto et al 2017 [7], once the data collection has been concluded, mean capacities installed per technology have been divided by their respective energy efficiency coefficients to obtain the work input (W) per equipment type. Then, in order to obtain energy consumption values per equipment type and sector, the number (Nr.)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the methodology proposed by Pezzutto et al 2017 [7], once the data collection has been concluded, mean capacities installed per technology have been divided by their respective energy efficiency coefficients to obtain the work input (W) per equipment type. Then, in order to obtain energy consumption values per equipment type and sector, the number (Nr.)…”
Section: Methodsmentioning
confidence: 99%
“…In 2015, EU's primary energy consumption accounted for about 1600 Mtoe/y, of which a major contribution is provided by heating and cooling (H&C) applications (about 800 Mtoe/y, including also industrial heat), followed by transport and electricity (about 490 Mtoe/y and 310 Mtoe/y respectively) [4][5][6][7][8]. Buildings are responsible for approximately 640 Mtoe/y, which corresponds to 40% of the whole EU primary energy consumption [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This factor is obtained by dividing the cooling EIR (energy input ratio, this is the inverse of the cooling COP ratio) at each pair of temperatures and at full load by the nominal cooling EIR. Similarly to the cooling capacity, these results can be input to the EnergyPlus model as a table or as a performance curve by fitting them to Equation (5).…”
Section: Vrf System Modelmentioning
confidence: 99%
“…Buildings with diverse, multiple zones requiring individual control (office buildings, schools, hotels) are all good candidates [4]. VRF systems were reported as one of three most efficient systems when comparing different technologies installed in Europe, as well as one of the systems with the highest cooled floor area in commercial buildings such as offices and hotels [5].…”
Section: Introductionmentioning
confidence: 99%